Binge drinking in high school students from Fafe, Portugal: prevalence and associated factors. (30th September 2020) - Fernandes, S; Pardo, M
Abstract: Background: Binge drinking is defined, by 5 or more doses of alcohol on a single occasion (4 or more, in case of women). The excessive alchool consumption is the behavior with the most significant impact on youth mortality and morbidity. Binge drinking is a public health problem that can be preventable. The aim of this investigation was to estimate the prevalence of binge drinking and analyze the associated factors to this behaviour among high school students from Fafe, Portugal. Methods: Cross-sectional study. Invited 1334 high-school students, aged between 15 and 19 to fill in an anonymous self-administered digital survey between May and June 2019, wich includes questions about alcohol sociodemographic characteristics, physical activity and smoking. Associations between binge drinking in the last 2 months and the several factors were analyzed through multivariated logistic regression, using IBM SPSS v.20, considering a significance level of 5%. Results: A total of 786 students answered the survey (response rate 58.9%), 714 surveys were validated. The median age of participants was 17(1.074 sd) years and 54, 8% were girls. The proportion of students from academic high school were 70.9%. Considering all the students estimated binge drinking prevalence was 28.6% (95%IC:25.35-31.79) and 41, 5% (95%IC:36.9-45.8) within who have reported to drink. Binge drinking was associated with male gender (OR = 1.75; 95%IC:1.186-2.585), regulary cigarrete smoking (OR = 7.48; 95%IC: 3.422-16.347), being on 12th grade (OR = 2, 677; 95%IC:1.625-4.412). There wasńt found association on binge drinking proportion between students from academic or vocational school. Conclusions: Our study concluded that binge drinking is common among Fafe high school students. This study provides relevant information to public health authorities about the binge drinke behaviour on this population and makes possible to identify the most high-risk students of binge drinking in order to planning interventions. Key messages: Binge drinking pattern is increasing among adolescents and young adults. Future preventive interventions on binge drinking are importante and should consider the associated factors of this behaviour.